2014
DOI: 10.1155/2014/258614
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Employment Integration, Mental Illness and Disability, and Workplace Health

Abstract: This paper reviews the literature on the interplay between employment integration and retention of individuals diagnosed with mental health and related disability (MHRD). Specifically, the paper addresses the importance of an integrative approach, utilizing a social epidemiological approach to assess various factors that are related to the employment integration of individuals diagnosed with severe mental illness. Our approach to the review incorporates a research methodology that is multilayered, mixed, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…A multi-country exploratory survey in Europe revealed the willingness of employers to improve inclusion in the workplace and their need for specialist assistance to provide accommodation in the workplace for persons with mental disabilities [16]. However, a review by Khalema and Shankar suggested that globally, the majority of employers are unwilling to employ persons with severe mental illness on account of their perceived poor work ability [17]. According to Krupa et al there are many myths about the work ability of persons with a mental illness.…”
Section: Research Papermentioning
confidence: 99%
“…A multi-country exploratory survey in Europe revealed the willingness of employers to improve inclusion in the workplace and their need for specialist assistance to provide accommodation in the workplace for persons with mental disabilities [16]. However, a review by Khalema and Shankar suggested that globally, the majority of employers are unwilling to employ persons with severe mental illness on account of their perceived poor work ability [17]. According to Krupa et al there are many myths about the work ability of persons with a mental illness.…”
Section: Research Papermentioning
confidence: 99%
“…28 Premorbid factors such as education and employment history, illness-related factors such as negative symptoms, comorbidity and the need for frequent hospitalisation, social factors such as stigma and poor interpersonal skills, and environment-related factors such as low expectations, underestimation and/or underutilisation of skills, and restricted work project opportunities, are all likely to play a role. [27][28][29][30][31][32][33][34] Vocational support programmes that include inter agency collaboration and adhere to the individual placement and support (IPS) model with the use of an integrated community employment specialist, have been shown to be most effective in helping those with mental health disabilities gain and sustain employment, and should form part of any psychiatric rehabilitation service. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Given the high burden of physical health problems in people with SMD [56], this could have led us to incorrectly attributing impact on work impairment and food insecurity to SMD. We also did not measure medication side effects which could adversely affect work capacity [57], although most participants were not taking psychotropic medication at the time of the study. It is possible that poverty, disability, discrimination and poor social support are all proxies for more severe and enduring illness which is then associated with food insecurity, but this is unlikely as we were able to adjust for symptom severity and duration of illness.…”
Section: Strengths and Limitationsmentioning
confidence: 99%